Identidades e consciência histórica de jovens estudantes e professores de história: um estudo em escolas no meio rural e urbano - Silva Júnior, Astrogildo Fernandes da (2012)
This thesis had the objective to study the relation between identity formation and history consciousness from History teachers and youth students from the ninth year of fundamental cycle in rural and urban schools located in Araguari, Uberlândia and Patos de Minas, MG, Brazil. The specific objectives are: 1- To describe the scenario of the investigation: rural and urban area from Araguari, Uberlândia and Patos de Minas, Minas Gerais state and also to describe the public schools for basic education selected for this survey; 2- To identify and to analyze the socio-economical and cultural patterns; the meanings of youth condition; the values, references and perceptions from youth students from the last year of fundamental education in schools located in the rural and urban area; 3- To reflect about the process of identity formation and also the historical consciousness from History teachers working in the fundamental teaching in schools from the rural and urban area; To analyze how the Historical knowledge can help during the identity and history consciousness formation form teachers and youth students. This is a qualitative investigation ethnographic. In this context, we performed the following procedures: Bibliographical and documental studies; observation and field note annotation; elaboration and application of a questioner to the students; oral interview with directors and History professors; transcription and text formatting of the narratives and data consolidation by means of the Statistical Package for Social Sciences software SPSS. The study involved 130 youth students, six History teachers and six directors of the schools. The scenario of this investigation was Araguari, Uberlândia and Patos de Minas, Minas Gerais State, Brazil. In each municipality we chose two public schools, one located in the rural and the other in the urban area, making a total of six schools. The study revealed that the transformations occurred in the rural and urban area, from the research locus, showed some peculiarities and differences similar to those observed in other localities and regions from the country. It showed to be a complex scenario, ambiguous, marked by transitions, changes and traditions. The relations between rural and urban areas are circles and marked by interdependence. Youth students are plural social actors, expressing love, suffering, enjoyment, they think about their conditions and their life experiences, they showed to have a position toward their lives, they have desires and proposals of changing their life conditions. Also, they are critics concerning the scholar institution but they believe in school and trust their teachers. Turning to teachers, they express and reconstruct their personal and professional life history and in this sense, they build and transform their identities in the different places they act. Youth students attributed a positive meaning for History. Teachers express the desire to contribute for the formation of critical youth by means of different methodologies. However, the curriculum prescribed and the conditions of work in public schools make prevalent the teaching that follows straightly what is proposed by the didactic books, as long as traditional pedagogical practices, such as, abstracts written in the blackboard and memorization exercises. It was clear that the traditional perspective of History teaching prevailed restricted to the institutionalization. However, it showed some signs of a potential teaching turned to show the importance of a dynamic and critical historical consciousness. Even in front of adversities, we evidenced that teachers tried to teach History in a significant way for the youth students.